Soret and Dufor Effects on a Semi Infinite Inclined Plate - Palani, G.; Desdemona Kirubavathi, J.; Chandrasekaran, E. (International Journal of Engineering and Technology, 2018)
A numerical technique is used to study a thermo-diffusion and diffusion-thermo effects on a two dimensional, laminar, unsteady convective flow past an inclined plate. The basic equations of the flow problem are non-linear, coupled and integro partial differential equations, these equations are transformed into a dimensionless form and solve it numerically using well known Crank-Nicolson implicit finite difference method. Thermo-diffusion and diffusion-thermo effects on velocity, temperature, concentration, shearing stress, rate of heat and mass transfer are studied in detail.Â Â